Analysis Factors That Affecting the Incidence of Hypertension in Menopausal Woman: Analisis Faktor yang Mempengaruhi Kejadian Hipertensi Pada Wanita Menopause - Gita Maringga, Estin; Yunia Sari, Nunik Ike (Universitas Muhammadiyah Sidoarjo, 2020)
Hypertension is an increased incidence of blood pressure characterized by the increase of sistole and diastole. Hypertension if not properly administered, can cause a variety of complications such as stroke, heart failure, renal failure, encephalopathy, and others. Based on the statistical data of menopause women risk to experience hypertension of 41% compared with males. This research aims to analyze the risk factors that affect the incidence of hypertension in menopausal women in the village Kayen Kidul. The design of research in this study uses cross sectional, with the population is all menopause women who have hypertension in the village of South Kayen, using simple random samplling technique, obtained as many as 71 respondents . The variables in this study consist of a free variable that is age and a history of the use of KB and variables bound in the form of hypertension in menopausal women. The study was conducted on 16-21 September 2019, collecting data using interview and observation techniques using data collection sheets. Data analysts use linear regression, with calculations using SPSS. The results in this study were obtained from 71 respondents, 59.2% of the mother aged < 60 years, 69% had a history of hormonal contraceptives, 57.6% menopause had hypertension. The aged menopause ≥ 60 years and has a history of hormonal contraceptives have a greater risk of hypertensive incidence in menopause.